Long COVID-19: Psychological symptoms in COVID-19 and probiotics as an adjunct therapy - Angel Yun-Kuan Thye; Loh Teng-Hern Tan; Jodi Woan-Fei Law; Priyia Pusparajah; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
There is an increase in mental health sequelae following COVID-19 infection, with some studies showing a higher prevalence rate of psychiatric sequelae in post-COVID-19 survivors than in the general population. This review discusses the possible causes, prevalence, and risk factors of COVID-19 associated psychological manifestations, namely anxiety, depression, and post-traumatic stress disorder (PTSD). Although the exact cause is yet to be determined, it is likely multifactorial involving environmental, biological, and psychological factors due to the pandemic. Variation exists for risk factors and prevalence, but the female gender and psychiatric disorder history seem to be consistent risk factors across several studies. While conventional psychotropic medications are the common therapeutic intervention, probiotics could be a potential adjunct treatment to prevent and treat COVID-19 and its associated psychological manifestations. Their anti-inflammatory effects have been seen directly via reducing plasma concentration of proinflammatory cytokines or indirectly via the suppression within the kynurenine pathway and restoration of gut permeability. Additionally, short-chain fatty acids (SCFAs) are crucial gut microbial metabolites with essential roles, including signaling along the microbiota-gut-brain (MGB) axis, maintaining blood-brain barrier’s (BBB) integrity, neuronal functions, neurotransmitters, and neurotrophic factors modulation.